Thermal Analysis on Transformer In Substation: Transformer Material Selection - MUTHAZA, MUHAMMAD ZULQARNAIN; Sim Sy Yi; Zulkifli, Mardzulliana (Progress in Engineering Application and Technology, 2022)
A transformer substation is an electrical system that includes switchgear as well as distribution and transmission line terminations. Transformer substations convert voltage from high to low or possibly even better. The thermal performance of power substations is a major topic, especially for distribution networks. The heat produced by the transformer operation elevates the temperature of the transformer’s internal structures. More efficient transformers have a lower temperature rise, whereas less efficient units have a higher temperature rise. One of the main sources of damage is heat damage to the transformer windings during regular operation. Thermal method analysis, which is simulation software, SolidWorks was used to evaluate thermal performance. So in this project, the simulation Solidwork is used to simulate the thermal analysis in rising temperature and heat flux by comparing two material cores, which are amorphous metal and amorphous steel. From this simulation, the result is help in choosing suitable material due to the thermal cause compared to physical test that had limitation on the thermal result. From the simulation between amorphous metal and amorphous steel, the result shows a maximum temperature is 60 degree Celsius. For heat flux result shows an initial value reaching is 6.00+04 W/m2, and the thermal conductivity of metal is increase to 60 degrees Celsius. From that result, amorphous metal were proposed for suitable material core transformer